The coronavirus as break boundary: Navigating new landscapes in New Brunswick education - McGuire, Matthew R. T. (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2026)
The coronavirus caused a break boundary in public schooling. High school teachers in New Brunswick, Canada, were forced to confront a sudden shift in how they educated students — from classroom to computer screen. This qualitative interpretive case study investigated the reshaping of New Brunswick high school pedagogy prompted by an intensive turn toward digital technologies as a response to the pandemic. Data was thematically analyzed from the interviews of eight high school teachers who taught in a blended learning environment during the first full year of the pandemic. By listening to the voices and experiences of teachers, educational scholars and curriculum reformers can better understand how this unique educational event impacted teaching and learning and its implications for public schooling.